Estimates for the Cauchy matrix of perturbed linear impulsive equation - P. S. Simeonov; D. D. Bainov (International Journal of Mathematics and Mathematical Sciences)
Estimates for the Cauchy matrix of a perturbed linear impulsive equation are obtained for given estimates for the Cauchy matrix of the corresponding unperturbed linear impulsive equation.